Predictors of Intervention Success in a Sports-Based Program for Adolescents at Risk of Juvenile Delinquency. (May 2018) - Spruit, Anouk; van der Put, Claudia; van Vugt, Eveline; Stams, Geert Jan
To prevent juvenile delinquency, there is growing interest in the use of sports-based interventions. To date, there is little empirical research that provides insights into for whom, how, and when sports-based crime prevention programs are most effective. Therefore, the current study assessed which youth, coach, and context factors were predictive of change in risk factors and protective factors for delinquency in a sports-based crime prevention program for at-risk adolescents. Participants ( N = 155) and their teachers filled in questionnaires about risk and protective factors for delinquency at the start of the intervention and 13 months later. In addition, the coaches and participants filled in questionnaires about the predictors of intervention success. The youths showed significant improvements over the course of the intervention. Various youth, coach, and context factors (e.g., the type of education of youth and the sociomoral climate at the sports club) were associated to change in the outcome variables.